Midterm renal functions following acute renal infarction. Issue 10 (24th August 2015) - Ongun, Sakir; Bozkurt, Ozan; Demir, Omer; Cimen, Sertac; Aslan, Guven
Abstract: The aim of this study was to explore clinical features of renal infarction (RI) that may have a role in diagnosis and treatment in our patient cohort and provide data on midterm renal functions. Medical records of patients with diagnosis of acute RI, established by contrast enhanced computed tomography (CT) and at least 1 year follow‐up data, who were hospitalized in our clinic between 1998 and 2012 were retrospectively reviewed; including descriptive data, clinical signs and symptoms, etiologic factors, laboratory findings, and prescribed treatments. Patients with solitary infarct were treated with acetylsalicylic acid (ASA) only, whereas patients with atrial fibrillation (AF) or multiple or global infarct were treated with anticoagulants. Estimated Glomerular Filtration Rate (eGFR) referring to renal functions was determined by the Modification of Diet in Renal Disease (MDRD) formula. Twenty‐seven renal units of 23 patients with acute RI were identified. The mean age was 59.7 ± 15.7 years. Fourteen patients (60.8%) with RI had atrial fibrillation (AF) as an etiologic factor of which four had concomitant mesenteric ischemia at diagnosis. At presentation, 20 patients (86.9%) had elevated serum lactate dehydrogenase (LDH), 18 patients (78.2%) had leukocytosis, and 16 patients (69.5%) had microscopic hematuria. Two patients with concomitant mesenteric ischemia and AF passed away during follow up. Mean eGFR was 70.8 ± 23.2 mL/min/1.73 m 2 at admission and increased to 82.3 ± 23.4 mL/min/1.73 m 2 at 1 year follow up. RI should be considered in patients with persistent flank or abdominal pain, particularly if they are at high risk of thromboembolism. Antiplatelet and/or anticoagulant drugs are both effective treatment options according to the amplitude of the infarct for preserving kidney functions.